Intellectuals and the Corona Crisis: From Self-Reflection to Criticism of the Political and Strategies of Globalization - Al Shalabi, Jamal; Burqan, Asem (Dirasat: Human and Social Sciences, 2022)
The present study aims to highlight the most important axes of discussion and intellectual debate generated by the Corona virus at the end of the year 2019, in the intellectual and political arena in the world between thinkers and intellectuals, remotely from political argumentation between China and the United States regarding the responsibility of each side for the spread of the virus on the one hand, and irrespective of their differing ideological orientations on the other hand, as manifested and exemplified in the arguments of: Carolin Emcke, the Moroccan poet Muhammad Bnais, the two French philosophers Michel Onfray, Edgar Morin, and the American intellectual Naom Chomsky, and others. The study reached two conclusions: First: As a consequence of the feeling of "collective danger" which assaulted the world and humanity, there arose an orientation among intellectuals and thinkers advocating a return to "common roots" which unify humanity, and which impel it to solidarity to confront the overarching common challenges besetting the world and the universe. Second: There is almost total unanimity among the intellectuals and thinkers that notwithstanding the fact that globalization constitutes a "cornerstone" in the progress of humanity and its movement towards the future, it nevertheless represents a "wild capitalism" which rendered the Corona pandemic for the thinkers and intellectuals a "historic opportunity" to restore importance to the individual and humanity in "building the future